Effects of supplementing dried distillers grains with solubles to yearling stocker cattle during the last 90 days of grazing on animal performance, carcass characteristics and meat quality when utilizing a short feeding protocol - Stickel, Andrew Dale (Kansas State University, 2012)
Crossbred yearling steers (n = 144 initial BW 367 ± 18.46 kg) were randomly allotted by BW to a randomized complete block design with a 2x3 factorial treatment arrangement to 1) assess the impact of supplementing dried distiller grain with solubles (DDGS) while grazing late season forage for 90 d and 2) the impact of a short feeding period on animal performance, carcass characteristics and meat quality traits. Treatments consisted of DDGS supplementation during grazing (0 or 1% of BW as DDGS; DM basis) and finishing days on feed (DOF;75, 100, 125). During grazing supplemented cattle had greater (P < 0.01) ADG than un-supplemented cattle but un-supplemented cattle had greater ADG than supplemented cattle during the finishing period. There were no differences between grazing treatments for DMI (P = 0.91) during the finishing period. Supplemented cattle had decreased (P = 0.02) G:F during the finishing period compared to un-supplemented cattle. Supplemented cattle had heavier (P < 0.01) HCW and larger (P = 0.02) LM area than un-supplemented cattle. Increasing DOF linearly increased (P ≤ 0.03) HCW, 12th rib fat thickness, LM area and USDA marbling score. No differences were observed for USDA yield grade. Increasing DOF decreased (Linear; P < 0.01) carcass protein %, moisture %, and increased (Linear; P < 0.05) carcass fat %. Increasing DOF increased (Quadratic; P = 0.01) L* values, while decreasing (Quadratic; P < 0.01) a* and b* values for external fat color. No differences were observed with respect to the percentages of any fatty acids for any treatment. Increased (P = 0.01) sensory off-flavors were present at 100 DOF when compared to 125 DOF. No other differences among treatments were observed for any sensory traits, instrumental tenderness, lean color or fatty acid profile for any treatment. In conclusion, supplementing cattle with 1 % DDGS during grazing altered grazing and feedlot performance as well as impacted carcass characteristics. In addition, utilizing a shortened feeding period had minimal effects on meat quality traits, but increasing DOF resulted in a greater amount of whiter external fat.
Keywords: Beef; Days on feed; Dried distiller’s grains with solubles; Fat color; Grazing; Animal Sciences (0475)